Genetic analysis and diversity studies in sesame (Sesamum indicum L.): GENETIC ANALYSIS AND DIVERSITY STUDIES IN SESAME - S R KUMHAR; RAJANI BISEN (Journal of Oilseeds Research, 2021)
Genetic variability, path coefficient and diversitywere studied using 56 genotypes ofsesame [Sesamum indicum (L.)] in RBD with three replications at Agricultural Research Station, Mandor, Jodhpur during kharif 2019. The mean squares for all the characters were significant indicating the presence of wide genetic variability. The high magnitudes of PCV and GCV for seed yield and moderate values for primary branches/plant depicted the presence of high amount of variation. High heritability coupled with high genetic advance for seed yield suggesting that it could be improved through direct selection due to predominant additive variation. High heritability with moderate genetic advance as 5% of mean were observed for plant height and 1000 seed weight indicating the influence of non-additive gene action in the expression ofthese traits. Correlation coefficient analysis showed that seed yield had significant positive association with number of capsules/plant followed by 1000 seed weight and oil content at both genotypic and phenotypic level. Path coefficient analysis revealed that number of capsules/plant possess the highest positive direct effect (0.473) followed by 1000 seed weight (0.432) and plant height (0.313) on seed yield, which suggested that during selection more emphasis should be given to these characters to develop a desirable plant type. In the diversity study, the maximum intra-cluster distance was estimated in cluster-VIII (11.77) followed by cluster-VI (10.74), cluster-I (8.94), cluster-II (8.76), cluster-III (7.11) and cluster-IV (5.12) indicating wide genetic variability within the genotypes of these six clusters. The maximum inter-cluster distance was estimated between cluster-III and VIII (69.10) followed by cluster-III and IV (62.33) and cluster-III and VI (62.24), suggesting wide diversity between genotypes of these clusters.